2021
DOI: 10.1038/s41598-021-85960-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic changes of Interleukin-12/15/18-stimulated human NK cells

Abstract: Natural Killer (NK) cells acquire memory-like properties following a brief stimulation with IL-12, IL-15 and IL-18. These IL-12/15/18-preactivated NK cells, also known as cytokine-induced memory-like (CIML) NK cells, have been revealed as a powerful tool in cancer immunotherapy due to their persistence in the host and their increased effector functions. Several studies have shown that NK cells modulate their metabolism in response to cytokine-stimulation and other stimuli, suggesting that there is a link betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 67 publications
0
38
0
Order By: Relevance
“…In fact, increased glycolysis was shown to be correlated with MCMV-mediated adaptive NK cells [ 67 ], pointing to the metabolic changes in the NK cells that may play a vital role in their effector functions and recall responses [ 44 ]. A very recent study by Terrén et al showed that expression of nutrient transporters including transferrin receptor (CD71), amino acid transporter (CD98) and glucose transporters (GLUT1 and GLUT3) was increased after NK cells were exposed to CIML conditions [ 68 ]. Importantly, the CIML NK cells preserved elevated expression of amino acid transporters even in the resting phase.…”
Section: Innate Memory In Nk Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, increased glycolysis was shown to be correlated with MCMV-mediated adaptive NK cells [ 67 ], pointing to the metabolic changes in the NK cells that may play a vital role in their effector functions and recall responses [ 44 ]. A very recent study by Terrén et al showed that expression of nutrient transporters including transferrin receptor (CD71), amino acid transporter (CD98) and glucose transporters (GLUT1 and GLUT3) was increased after NK cells were exposed to CIML conditions [ 68 ]. Importantly, the CIML NK cells preserved elevated expression of amino acid transporters even in the resting phase.…”
Section: Innate Memory In Nk Cellsmentioning
confidence: 99%
“…The study also reported that CIML NK cells undergo metabolic switch toward glycolysis which persists even after the cytokine withdrawal. Detailed analysis of the relation between glycolysis and effector function showed that the production of IFNγ and MIP-1β was sensitive to glycolysis inhibition, whereas other effector functions including TNFα secretion, degranulation and cytotoxic activity were not very sensitive to the glycolysis inhibition [ 68 ].…”
Section: Innate Memory In Nk Cellsmentioning
confidence: 99%
“…Therefore, such metabolic perturbations that impact upon Srebp activiation will prevent the innate training response in NK cells and the immunological advantages it affords. Recent work by Terren and colleagues investigated the metabolic requirements of cytokine trained NK cells and demonstrate a bias towards glycolysis (although it is noted that the levels of 2DG used in this study were enough to completely shut down all glycolytic activity of the cell) 36 . These studies did not investigate the requirements for training but the metabolism used by fully trained cells, but support the importance of metabolism for NK cell activity in line with our previous works 11,12,20,23,26 .…”
Section: Discussionmentioning
confidence: 82%
“…NK cells are known to develop normally in recombination activating genes 1 and 2 (Rag1/2) deficient mice where T cells and B cells are absent as reported in earlier studies [48][49][50]. Nonetheless, a later study reported that RAG-deficient NK cells exhibited a diminished survival capacity upon virus-driven proliferation, as well as defects in repairing…”
Section: Discussionmentioning
confidence: 92%